Friedelin and lanosterol from Garcinia prainiana stimulated glucose uptake and adipocytes differentiation in 3T3-L1 adipocytes - Darnis, Deny Susanti; Mohamed Amiroudine, Mohamed Zaffar Ali; Rezali, Mohd Fazlin; Bakhtiar, M. Taher (Taylor & Francis, 2012)
Friedelin and lanosterol have been isolated from twigs of Garcinia prainiana.Their structures were elucidated by spectroscopic methods. The compounds were examined for their effects on 3T3-L1 adipocytes. In the MTT assay, it was found that the compounds had no cytotoxic effects up to 25 mM. Adipocyte differentiation analysis was carried out by Oil Red O staining method. In the presence of adipogenic cocktail (MDI), it was found that friedelin and lanosterol enhanced intracellular fat accumulation by 2.02 and 2.18-fold, respectively, compared with the vehicle-treated cells. Deoxyglucose uptake assay was used to examine the insulin sensitivity of adipocytes in the presence of the compounds. It was found that friedelin was able to stimulate glucose uptake up to 1.8-fold compared with insulin-treated cells. It was suggested that friedelin and lanosterol may be beneficial to mimic insulin action that would be useful in the treatment of diabetes type 2 patients.